ENGLISH TEACHERS’ VERBAL INSTRUCTIONS - Rida Marlenie (Corolla International Conference, 2022)
The aims of this research were to find out the dominant language the teachers used in giving verbal instructions and the proportion of the teachers’ instruction forms. This research employed descriptive method. The research observed the teachers in the English classroom. From the observation, it was found teacher 1 used English more than Indonesian language, she used imperative form as the dominant form in English and declarative form in Indonesian language. Teacher 2 also used English more than Indonesian language, which the most frequency form was imperative in both English and Indonesian. It was also happen to teacher 3. Meanwhile, teacher 4 used Indonesian more than English, which the dominant form was imperative. Based on the data of each teacher’s instructions, the percentage of languages used by the English teachers in giving the instructions was in English 59,9% and 40,1% giving in Indonesian language. The imperative was the most frequency used by teachers in both Indonesian (78,68%) and English (68,65%). The other forms in English were interrogative in second position (23,19%) and the last was declarative (8,16%). In Indonesian language in second position was interrogative (15,51%) and the last was declarative(5,81%).